The Profile of Patients with Allergic Rhinitis Before and During the Covid-19 Pandemic - Dwi Angga, Dendy Bahtiar; Pawarti, Dwi Reno (Journal of Neonatal Surgery, 2025)
Background: Allergic rhinitis is an inflammatory reaction of the nasal mucosa mediated by IgE after exposure to an allergen as an immunological response, with classical symptoms such as a runny nose, sneezing, stuffy nose, nasal itching, red and watery eyes, and discomfort at the hard palate. The number of patients with allergic rhinitis who came to the hospital during the COVID-19 pandemic was affected by the increasing number of cases. The number of patients from March 2018 to February 2020 was 234, while the number of people from March 2020 to February 2022 was 59. Objective: To identify the profile of patients with allergic rhinitis. Methods: This research is a retrospective descriptive study using secondary data from medical records. The study population was patients with allergic rhinitis who visited the Allergy-Immunology Division of ORL-HNS outpatient department, Dr. Soetomo General Hospital, Surabaya, from March 2018 to February 2022. Results: There were a total of 357 people, but only 293 people were included in the research inclusion and exclusion criteria, with the distribution of female patients was 40.96%, the age group of 20-59 years, at 49.49%, and the highest distribution of jobs was entrepreneurs, at 24.23%. The most common symptoms were a runny nose at 24.69%, the most quantitative Total Nasal Symptom Score moderate (5-8) at 47.44%, and the highest moderate-severe persistent classification at 33.79%. Conclusion: The results showed that there was no significant relationship between age and Total Nasal Symptom Score of the patients, and there is a significant relationship between gender, jobs, clinical symptoms, and classification of allergic rhinitis according to ARIA-WHO of patients who arrived before and during the COVID-19 pandemic.